KETETAPAN DAN PERATURAN DALAM KITAB ULANGAN 12-28 SERTA IMPLEMENTASINYA DALAM PEMBINAAN WARGA GEREJA - Pane, Pranada (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2025)
In the explanation of the Book of Deuteronomy 12-28, it tells about the decrees and regulations given by the Lord God to the Israelites and this was conveyed through Moses. This is conveyed with the aim of guiding their lives in obedience to Allah and the formation of a just society. These provisions cover various aspects, ranging from correct worship, social rules, family law, to instructions regarding moral and ethical life. The discussion in these articles emphasizes the importance of pure worship of God, protection of the weak, and enforcement of just laws in Israeli society. In the context of contemporary church life, the implementation of these decrees and regulations can be seen in the formation of church members which includes moral teaching, strengthening the discipline of Christian life, as well as applying the values of justice and love in relationships between congregations. This formation serves to strengthen faith, build solidarity, and form Christian character that prioritizes living in truth, love, and perseverance towards God. Thus, even though these regulations were revealed in the context of ancient times, the values contained in them are still relevant and can even be implemented in the guidance that the church carries out for the lives of the congregation entrusted to the church so that they experience changes in life and growth. spiritually and obtain the teachings of God's Word to use as a guide and testimony for the life of the congregation